Ionic liquids pretreatment for fabrication of agro-residue/thermoplastic starch based composites: A comparative study with other pretreatment technologies - Mahmood, H. (Elsevier Ltd, 2017)
Ionic liquids (ILs) pretreatment has emerged as a promising technology toward environmentally benign conversion of lignocellulosic residues into high value cellulosic fiber as sustainable raw material for biocomposite fabrication. This study presents a comparison of ILs-assisted pretreatment of oil palm fronds (OPF) fiber with dilute acid, alkaline, and hot compressed water pretreatments on the mechanical and thermal properties of their fabricated thermo-molded biocomposites with thermoplastic starch as a biopolymer binder. A comparison of energy consumption for ILs pretreatment with other pretreatment methods was also performed and the comparative impact of ILs pretreatment on OPF fiber was investigated by lignocellulosic composition, crystallinity and thermal stability analysis for untreated and all pretreated fibers. Results indicate that ILs pretreatment is superior in terms of delignification of OPF and produces cellulose rich fiber (CRF) with 48–50 reduced crystallinity as compared to those of acidic, alkaline, and hot water pretreated fibers. However, the flexural strength of the IL emimdep treated composite (13.8 MPa) was significantly improved over that of untreated composite with value of 5.3 MPa, but was slightly higher than acidic and hot water pretreatments which were 13.5 MPa and 10.8 MPa, respectively. ILs pretreatment consumed about 0.5–2.0 folds more energy per kg of OPF residue as compared to other methods. In the premises of the present findings, we believe that ILs-based pretreatment could be a new, clean and promising alternative processing approach for conversion of a wide variety of agro-based lignocellulosic waste materials into cellulose-rich fibers for manufacturing of engineered biocomposite panels. © 2017 Elsevier Ltd